2021
DOI: 10.52628/87.3.03
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant ipsilateral acetabular and femoral fractures – an appraisal of outcomes and complications in 34 patients

Abstract: Concomitant ipsilateral femoral and acetabular fractures are complex injuries which result from high-velocity trauma. Surgical treatment is the accepted management of such injuries. The objectives of this study were to evaluate the outcomes and study the complications in patients treated for concomitant ipsilateral acetabular and femoral fractures (type ‘B’ floating hip injuries). This retrospective study was conducted at a tertiary care teaching hospital on patients operated for type B floating hip injuries,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“… 3 , 5 , 8 , 11 , 13 Nonetheless, some studies have suggested pelvic fractures should be addressed first if the pelvis is a significant source of bleeding, and may potentially precipitate haemodynamic instability. 12 , 19 , 22 Interestingly, Audretsch et al 16 and Wu et al 22 reported observing no significant differences in outcomes between a femur first versus pelvic/acetabular first strategy in managing FH cases.…”
Section: Discussionmentioning
confidence: 99%
“… 3 , 5 , 8 , 11 , 13 Nonetheless, some studies have suggested pelvic fractures should be addressed first if the pelvis is a significant source of bleeding, and may potentially precipitate haemodynamic instability. 12 , 19 , 22 Interestingly, Audretsch et al 16 and Wu et al 22 reported observing no significant differences in outcomes between a femur first versus pelvic/acetabular first strategy in managing FH cases.…”
Section: Discussionmentioning
confidence: 99%